2021
DOI: 10.3390/soc11030070
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Interpreters in Medical Education: A Narrative Literature Review

Abstract: This paper presents the results of a narrative literature review on the use of interpreters in medical education. A careful search strategy was based on keywords and inclusion and exclusion criteria, and used the databases PubMed, Medline Ovid, Google Scholar, Scopus, CINAHL, and EBSCO. The search strategy resulted in 20 articles, which reflected the research aim and were reviewed on the basis of an interpretive approach. They were then critically appraised in accordance with the “critical assessment skills pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…The use of interpreters in medical education was discussed in Constantinou et al's [21] literature review of 20 papers, which showed that the use of interpreters as part of medical curricula was scarce, although students were trained in how to work with interpreters in programmes largely outside their curriculum. The trainings showed that students improved their skills and helped them provide better care to patients.…”
mentioning
confidence: 99%
“…The use of interpreters in medical education was discussed in Constantinou et al's [21] literature review of 20 papers, which showed that the use of interpreters as part of medical curricula was scarce, although students were trained in how to work with interpreters in programmes largely outside their curriculum. The trainings showed that students improved their skills and helped them provide better care to patients.…”
mentioning
confidence: 99%